Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Plasma activated water offers food security opportunities by increasing shelf life of freshwater fisheries products in South Africa - Kay Howard; Frederich Henneke; Olivia J. B. Chalwin-Milton; Carel J. Oosthuizen; Peter Johnston; Kirsty L. Bayliss (Food Security, 2023)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Metabarcoding shows multiple Phytophthora species associated with individual plant species: implications for restoration - Jamba Gyeltshen; William A. Dunstan; Christopher Shaw; Kay Howard; Andrew H. Grigg; Giles E. St. J. Hardy; Treena I. Burgess (European Journal of Plant Pathology, 2021)

Role of salicylic acid in phosphite-induced protection against Oomycetes; a Phytophthora cinnamomi - Lupinus augustifolius model system - Emma Groves; Kay Howard; Giles Hardy; Treena Burgess (European Journal of Plant Pathology, 2015)

Phosphite stimulated histological responses of Eucalyptus marginata to infection by Phytophthora cinnamomi - Roslyn A. Pilbeam; Kay Howard; Bryan L. Shearer; Giles E. St. J. Hardy (Trees, 2011)

The potential of copper sulphate to control Phytophthora cinnamomi during bauxite mining in Western Australia - Kay Howard; Ian J. Colquhoun; Giles Hardy (Australasian Plant Pathology, 1998)